2013
DOI: 10.1016/j.scitotenv.2013.03.083
|View full text |Cite
|
Sign up to set email alerts
|

Potential water quality impacts originating from land burial of cattle carcasses

Abstract: Among the conventional disposal methods for livestock mortalities, on-farm burial is a preferred method, but the potential water quality impacts of animal carcass burial is not well understood. Typically, on-farm burial pits are constructed without liners to prevent percolation of leachate into soil and groundwater. To date, no information is available on temporal trends for contaminants in leachate produced from livestock mortality pits. In our study, we examined the concentrations of conventional contaminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…), compared to the threshold value of 10 mg·L −1 in leachate from monitoring wells. Increased chloride concentrations (about 2600 mg·L −1 ) have been measured as well [5]. Pratt and Fonstad [9] have found that leachate components might vary depending on the type of buried animal carcass: poultry (NH 4 + -N at 10,400 mg·L −1 and Cl − at 2570 mg·L −1 ), cattle (NH 4 + -N at 14,100 mg·L −1 and Cl − at 2600 mg·L −1 ), and pig (NH 4 + -N at 13,300 mg·L −1 and Cl − at 2380 mg·L −1 ).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…), compared to the threshold value of 10 mg·L −1 in leachate from monitoring wells. Increased chloride concentrations (about 2600 mg·L −1 ) have been measured as well [5]. Pratt and Fonstad [9] have found that leachate components might vary depending on the type of buried animal carcass: poultry (NH 4 + -N at 10,400 mg·L −1 and Cl − at 2570 mg·L −1 ), cattle (NH 4 + -N at 14,100 mg·L −1 and Cl − at 2600 mg·L −1 ), and pig (NH 4 + -N at 13,300 mg·L −1 and Cl − at 2380 mg·L −1 ).…”
Section: Introductionmentioning
confidence: 90%
“…However, the pH of the burial pit soil was lower than surrounding soils. Such a decrease in pH might be due to bacterial fermentation products via metabolic processes which could convert sugar to acids, particularly under aerobic conditions [3,5].…”
Section: Removal Of Leachate Contaminants By Prbmentioning
confidence: 99%
See 3 more Smart Citations